(untitled) (Vojnotehnički glasnik / Military Technical Courier, 2021)
Ministry of Education, Science and Technological Development of the Republic of Serbia classified the Military Technical Courier for the year 2020. Pursuant to the decision given in Article 27, paragraph 1, point 4, and in accordance with the acquired opinion given in Article 25, paragraph 1, point 5 of the Act on Scientific and Research Activities (Official Gazette of the Republic of Serbia, No 110/05, 50/06-cor and 18/10), the Ministry of Education, Science and Technological Development of the Republic of Serbia classified the Military Technical Courier for the year 2020, on December 18, 2020.